ANALYSIS AND OPTIMIZATION OF URBAN-SUBURBAN 5G COVERAGE PREDICTIONS (FUDMA JOURNAL OF SCIENCES, 2024)
In today's world, the demand for robust and faster network connectivity and data speeds has become paramount. Though the transition to 5G technology is a significant advancement that promises unparalleled speeds, reduced latency, and enhanced connectivity crucial for modern applications, the current situation reveals persistent challenges in achieving these ideals across diverse environments. There are disparities between predicted and actual network performance metrics such as throughput, latency, coverage gaps, and inconsistencies in QoS (quality of service). The study aims to analyze the existing 5G coverage predictions and model a similar network scenario on MATLAB for optimization of the 5G network.
Keywords: 5G; Beamforming technology; SINR; KPI; 5G throughput